97 SYNERGISTIC ENHANCEMENT OF BREAST CANCER CHEMOTHERAPY BY PAR1 PEPDUCINS. (1st March 2007) - Yang, E. J.; Agarwal, A.; Nguyen, N.; Kuliopulos, A.; Covic, L.
Abstract : Protease-activated receptor 1 (PAR1) belongs to a unique family of G protein-coupled receptors that carry their own tethered ligand at the extracellular domain. Upon proteolytic cleavage, the ligand is exposed and is allowed to intramolecularly self-activate, triggering a cascade of signaling events leading to changes in cell shape, proliferation, migration, secretion, adhesion, and gene transcription. PAR1 is identified as an oncogene, and its expression is implicated in the development and metastasis of cancers of the breast, ovary, prostate, lung, pancreas, colon, and skin. The level of PAR1 expression correlates directly with the degree of invasiveness in primary breast tissue and established cancer cell lines. Most notably, PAR1 expression alone is sufficient in increasing migration, invasion, and tumor formation in the PAR1-null, minimally invasive MCF-7 breast cancer cell line. Conversely, silencing of PAR1 expression in the PAR1-positive, highly invasive MDA-MB-231 breast cancer cell line decreases migration and invasion. Here we investigate the potential of PAR1 as a target for cancer chemotherapy, using a powerful pepducin-based technology as a PAR1 inhibitor. Pepducins are palmitoylated cell-penetrating peptides that act as intracellular inhibitors of PAR1-G protein signal transference. We observe that pepducin therapy decreases cell proliferation and increases apoptosis in MDA-MB-231 cells and suppresses tumor growth in a xenograft model in which MDA-MB-231 cells are injected into the mammary fat pads of athymic nude mice. The use of two or more chemotherapy drugs in combination is thought to offer a superior tumor response and is commonly practiced in cancer therapy. To investigate the effects of PAR1 inhibition in the context of combination therapy, pepducins were administered together with docetaxel, a microtubule-stabilizing chemotherapy drug used commonly in breast cancer treatment. Concomitant administration of pepducin and docetaxel showed significantly enhanced tumor growth suppression in the xenograft model. In fact, when pepducin and docetaxel were administered together at doses that are individually ineffective, tumor development from MDA-MB-231 cells was almost completely abrogated. These results were supported by the MTT cell proliferation assay in which quantitative data analysis by the isobologram method revealed a highly synergistic interaction between pepducin and docetaxel. Put together, these in vitro and xenograft data suggest that therapeutics that block PAR1 signaling are beneficial in suppressing tumor development and support the potential of PAR1 as a viable target in cancer chemotherapy. Our current work involves the elucidation of the PAR1 signaling pathway and combination therapy synergy mechanism.